Game-theoretic analysis of the impact of differential leadership on employee silence behavior in Chinese family enterprises - Lu, Jie; Yang, Ting; Qin, Yi; Hu, Xinting (Frontiers in Physics, 2025)
In the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era, there is growing concern about the impact of differential leadership, a leadership style with localized characteristics, on employee perspectives and recommendations. This study constructs a dynamic game model to examine the influence of differential leadership on the silence behavior of insiders (employees perceived as close to the leader) and outsiders (employees perceived as distant from the leader). The results of the study found that both insiders and outsiders who want to achieve and sustain benefits need to demonstrate non-silent behaviors in order to gain the attention and goodwill of the leader. Insiders’ self-efficacy, outsiders’ out-group preference and employees’ proactive personality are the key factors driving their non-silence behaviors, constructing a constructive atmosphere in the organization, and bringing perceived benefits. This study provides relevant insights and reflections for the high-quality development of family enterprises. This study, on the one hand, addresses the research gap concerning self-perceived benefits and out-group favoritism within the organizational framework of family businesses against the backdrop of Chinese traditional culture. It establishes an analytical framework for the impact of “differential leadership-self-perceived benefits/out-group favoritism-employee silence behavior” in family businesses. On the other hand, it focuses the research lens on the relatively novel topic of the theoretical and practical examination of the relationship between differential leadership and employee silence behavior in family businesses. From a micro perspective, this study offers a new direction for Chinese family businesses to alleviate employee silence behavior and successfully achieve transformation.